Esvaziamento gástrico, sintomas gastroduodenais e qualidade de vida em pacientes com diabetes mellitus Tipo 1 - Saraiva, Larissa Gurgel Mota (2017)
Gastrointestinal clinics complaints are common in patients with longstanding type 1 diabetes mellitus (DM1) and some of these symptoms are closely linked to delayed gastric emptying (GE). Diabetic gastroparesis is a clinical condition defined by delayed gastric emptying. The aim of our study was to investigate the frequency and association of gastric emptying with gastroduodenal symptoms and quality of life (QOL) in patients with DM1. The study was performed at the endocrinology clinic of a tertiary-level hospital in the State of Ceará. The sample consisted of 48 participants. Glycated hemoglobin and fasting glycemia were measured, as well as questions about the presence of chronic complications. GE of solids was evaluated by respiratory test with the use of octanoic acid bound to carbon with the calculation of tlag and t1 / 2. The questionnaire "Gastropearesis Cardinal Symptom Index" was used for evaluation of symptoms of gastroparesis and the dyspeptic symptoms were evaluated through the Porto Alegre questionnaire for dyspeptic symptoms (PADYQ). Quality of life was assessed by the questionnaire "The Medical Outcomes Study 36-Item Short Form Health Questionnaire" (SF-36). In solids GE, patients with DM1 had a slower GE when compared to healthy controls. Most patients with slow GE had dyspeptic and / or gastroparesis symptoms. Patients with DM1 with slow GE had a significantly higher score of gastroparesis and dyspepsia when compared to normal GE patients. No statistically significant correlations were observed between GE with glycated hemoglobin, fasting glycemia or presence of chronic complications of diabetes. Six dimensions of QOL presented lower scores among patients with slow GE compared to patients with normal GE, with emphasis on the social aspects dimension. CONCLUSION: Patients with DM1 presented slower GE when compared to healthy controls. The overall scores of gastroparesis and dyspeptic symptoms and changes in QOL dimensions are associated with delayed GE.